“Serve and Ngalap berkah”: Motivation to be An Islamic Boarding School Teacher - Najib, Khotim Hanifudin; Mushodiq, Muhamad Agus; Widayat, Prabowo Adi; Djufri, Elyas (Balai Diklat Keagamaan Ambon, 2024)
Many studies have been conducted in various countries exploring why people become school teachers. However, only some have explored why someone becomes an Islamic boarding school teacher. This article explores why someone is becoming a teacher at an Islamic boarding school. This case study research was conducted by interviewing teachers at the Nurul Ummah Islamic Boarding School in Yogyakarta. A total of 8 teachers shared their experiences while being teachers at the Islamic boarding school. The research results show that teachers teaching at Islamic boarding schools are motivated to serve and